El mundo de la realidad Virtual y aumentada en baja visión - Valderrama Muñoz, Daniela (Universidad Antonio Nariño, 2022)
Currently there is a great advance in technology regarding the use of virtual and augmented reality focused on video games and other entertainment activities; thus taking advantage of the characteristics of techniques used as retinal stimulator in therapeutic treatments for patients with low vision. Although there are studies on the therapeutic effect on general health and some visual functions, this study seeks to demonstrate the differences between virtual and augmented reality, thus analyzing the advantages and disadvantages of each of them